The dark side of socialization: How and when divestiture socialization undermines newcomer outcomes. (17th January 2019) - Montani, Francesco; Maoret, Massimo; Dufour, Lucas
Summary: This research examines the potential downsides of divestiture socialization. We theorize that supervisor behaviors and attitudes—that is, support for authenticity and creativity expectations—moderate the different stages of a model in which newcomers' authentic self‐expression mediates the negative effect of divestiture socialization on newcomer task performance, creativity, social integration, and job satisfaction. Specifically, supervisor support for authenticity allows newcomers to express their authentic self when faced with divestiture processes, and perceived supervisor creativity expectations enable them to deploy their authentic self‐expressions to enhance their creativity. A time‐lagged, multisource study of 142 newcomer—supervisor dyads provides support for these predictions, offering notable implications for theory and practice.